Glutarate tunes T cell fate - Yanqui-Rivera, Francisco; Opitz, Christiane (Nature metabolism, 2023)
In this issue of Nature Metabolism, a study shows that glutarate increases memory T cells as well as T cell cytotoxicity and reduces tumour growth. During T cell activation, glutarate levels and glutarylation increase. Glutarate inhibits α-ketoglutarate-dependent dioxygenases, and glutarylation reduces pyruvate dehydrogenase complex activity and enhances glycolysis.
Gesehen am 10.06.2024